Comparative Analysis of Verbal Communication Vocabulary between Indonesian-Afrikaans for Foreign Language Teaching - Istanti, Wati; Seinsiani, Izzati Gemi; Visser, Johannes Gerhardus; Lazuardi, Ahlul Izza Destian (Universitas Negeri Makassar, 2020)
Every nation has its own language with distinctive features and historical background that differentiate between one another. Indonesian language and Afrikaans language is regarded to possess several historical resemblances. Indonesia was once colonized by the Dutch for 350 years, and therefore, some of the words or language structure in Indonesian language are influenced by Dutch language. In the meantime, South African people in the northern part of the country are very familiar with Dutch language. The study found out several similar words between Indonesian and Afrikaans language. The unique variations discovered in this study comprised: 1) similar spelling and pronunciation, 2) different spelling but similar pronunciation, 3) similar spelling but different pronunciation, and 4) almost similar spelling and pronunciation, but with similar meaning. Therefore, both languages are comparable in terms of identifying similarities and differences between both languages’ sound and spelling. The study intended to provide a reference for the Indonesian Language for Foreign Learners (Bahasa Indonesia bagi Penutur Asing, or henceforth, BIPA) teachers that conduct language teaching to the BIPA learners from South Africa. Vice versa, the BIPA learners will be able to comprehend Indonesian words following the dissemination of language kinship between Indonesian and Afrikaans language. Following that, the BIPA learning process will be more effective.Keywords: comparative analysis, conversation vocabulary, verbal language, Indonesian Language, Afrikaans